pr000024: Emile Vandervelde. Quarante croquis et dessins - Lucifer (1932)
"Collection: Emile Vandervelde. Quarante croquis et dessins; Prent in zwart-wit voorstellend Emile Vandervelde. Tekst : une attitude d'Emile Vandervelde. Series: Emile Vandervelde. Quarante croquis et dessins; FULL TEXT AVAILABLE AT AMSAB-ISH"